(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
In this article the main tendencies of Frankenstein’s line transformations of the beginning of the XXI century are analysed, in particular in representative for this context drama «I, Frankenstein» by Stuart Beattie. The logic of diffusion phenomenons in the reinterpretation of the key image is explained. It is shown the expansion of scopes of the art valense of the legendary-mythological structure in the fantasy environment.